The degree to which secondary school teachers practice the method of education with current events in light of Islamic education from the students’ point of view in Taif governorate: A field study - Althobaiti, Mohammed Ahmad Aldamouk (Journal of Educational and Psychological Sciences, 2020)
This thesis aims to identify the degree of secondary school teachers’ practice of current events education approach in the light of Islamic education. To achieve the objectives of the study، the researcher forms a questionnaire consisting of (35) items، it covers five aspects (religious، social، moral، political، economic، and health). The research tool’s validation and reliability are approved which are applied to a sample consists of (500) students. The research results conclude that: The degree of secondary school teachers’ practice of current events education approach in the light of Islamic education in Taif Province is medium in all aspects، with a mean of (3.02). The research suggests informing the secondary stage teachers of the positive effects of applying current events teaching method، because of its high impact on learning. Accordingly، the research also suggests training courses for teachers on how to practice current events method that is appropriate for the current era. As well as generalizing this method of teaching through media and educational institutions to reinforce and modify behavior.